Mechanical properties and mechanisms of soda residue and fly ash stabilized soil - Tianfeng Yang; Bo Huang; Chunan Zhan; Cheng Jiang; Liping Zhang; Xiaoqing Zhao; Mingrui Zhao (Scientific Reports)
Abstract To improve the utilization rates of soda residue (SR) and fly ash (FA), reduce environmental pollution, and enhance the mechanical properties of marine clay (MC), this study proposes mixing SR, FA, and MC with cement and /or lime to prepare soda residue-fly ash stabilized soil (SRFSS). Using an orthogonal design for the proportions, the study analyzes the compaction performance, unconfined compressive strength (UCS), and shear strength of SRFSS. The influence of various factors on the mechanical properties of SRFSS was investigated through range and variance analyses. The mechanical mechanism was revealed from the perspectives of grading and cementation. The results indicate that SR and FA significantly impact the mechanical properties of SRFSS. The range and variance analysis results are consistent: SR content of 30% and 70% has the most significant impact on compaction performance and UCS, respectively, while 20% FA content has the greatest effect on shear strength. The recommended base proportion is 70% SR + 20% FA + 10% MC. The gradation and cementitious properties jointly influence the mechanical performance and microstructure of SRFSS, G8 has the lowest planar porosity, at only 0.89%. The calcium (Ca) content in SRFSS specimens with different proportions shows significant variation, from 5.0 to 53.6 wt%, while the silicon (Si)/Al ratio (0.76–2.73) shows relatively small fluctuations. The primary hydration products include calcium hydroxide (Ca(OH)2), calcium silicate hydrate (C-S-H), and ettringite (AFt).